Effect of Earthworm Feeding Guilds on Ingested Dissimilatory Nitrate Reducers and Denitrifiers in the Alimentary Canal of the Earthworm - Depkat-Jakob, Peter S. (American Society for Microbiology (ASM), 2010)
The earthworm gut is an anoxic nitrous oxide (N(2)O)-emitting microzone in aerated soils. In situ conditions of the gut might stimulate ingested nitrate-reducing soil bacteria linked to this emission. The objective of this study was to determine if dissimilatory nitrate reducers and denitrifiers in the alimentary canal were affected by feeding guilds (epigeic [Lumbricus rubellus], anecic [Lumbricus terrestris], and endogeic [Aporrectodea caliginosa]). Genes and gene transcripts of narG (encodes a subunit of nitrate reductase and targets both dissimilatory nitrate reducers and denitrifiers) and nosZ (encodes a subunit of N(2)O reductase and targets denitrifiers) were detected in guts and soils. Gut-derived sequences were similar to those of cultured and uncultured soil bacteria and to soil-derived sequences obtained in this study. Gut-derived narG sequences and narG terminal restriction fragments (TRFs) were affiliated mainly with Gram-positive organisms (Actinobacteria). The majority of gut- and uppermost-soil-derived narG transcripts were affiliated with Mycobacterium (Actinobacteria). In contrast, narG sequences indicative of Gram-negative organisms (Proteobacteria) were dominant in mineral soil. Most nosZ sequences and nosZ TRFs were affiliated with Bradyrhizobium (Alphaproteobacteria) and uncultured soil bacteria. TRF profiles indicated that nosZ transcripts were more affected by earthworm feeding guilds than were nosZ genes, whereas narG transcripts were less affected by earthworm feeding guilds than were narG genes. narG and nosZ transcripts were different and less diverse in the earthworm gut than in mineral soil. The collective results indicate that dissimilatory nitrate reducers and denitrifiers in the earthworm gut are soil derived and that ingested narG- and nosZ-containing taxa were not uniformly stimulated in the guts of worms from different feeding guilds.